Stress Response Mechanisms in Fungi Theoretical and Practical Aspects (Springer International Publishing, 2018)
This book covers both the molecular basics of fungal stress response strategies as well as biotechnological applications thereof. The complex regulatory mechanisms of stress response pathways are presented in a concise and well-readable manner. Also, light will be shed on the interconnection of pathways responding to different types of stress. Profound knowledge of stress responses in yeast and filamentous fungi is crucial for further optimization of industrial processes. Applications are manifold, for example in fungicide development, for improving the resistance of crop plants to fungal pathogens, but also in medicine to help curing fungal infections. The book targets researchers from academia and industry, as well as graduate students interested in microbiology, mycology and biomedicine.